MÁRIO DE ANDRADE: A VIAGEM E O VIAJANTE - Maia, Gleidys Meyre da Silva (Organon, 2003)
The main purpose of this essay is to study the narrative traveland character-traveler’s image as discursive strategy of registration, identificationand representation of the nation, from the analysis of rhetoricalprocedures of representation of the other in the rhapsody Macunaíma oherói sem nenhum caráter, and in the reports of the ethnographical travel,between May and August 1927, gathered in the work O Turista Aprendiz.